Proteomic identification of predictive biomarkers for malignant transformation in complete hydatidiform moles. (February 2019) - Vanichtantikul, Asama; Hodge, Kenneth G.; Somparn, Poorichaya; Saethang, Thammakorn; Triratanachat, Surang; Pisitkun, Trairak; Lertkhachonsuk, Ruangsak
Abstract: Introduction: Protein expression in cells are associated with oncogenesis. This study aims to explore proteomic profiles and discover potential biomarkers that can predict malignant transformation of hydatidiform mole. Methods: Retrospective analysis was done in 14 cases of remission hydatidiform mole and 14 cases of hydatidiform mole who later developed malignancy (GTN group). Molar tissues were retrieved from −70 °C frozen tissue. Subsequently, a large-scale proteomic analysis was performed to identify proteins and compare their abundance levels in the preserved molar tissues from these two groups using a dimethyl-labeling technique coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: A total of 2, 153 proteins were identified from all samples. 22 and 10 proteins were significantly up-regulated and down-regulated, respectively, in the GTN group compared with the mole group. These altered proteins were found in several biological groups such as cell-cell adhesion, secreted proteins, and ribonucleoproteins. Several hormone-related proteins were among the most up-regulated proteins in the GTN group including choriogonadotropin subunit beta (β-hCG) and alpha (α-hCG), growth/differentiation factor 15, as well as both pregnancy-specific beta-1-glycoproteins 2 and 3. In contrast, protein S100-A11 andl -lactate dehydrogenase A chain, were down-regulated in molar tissue from most patients in the GTN group. Discussion: This study identified a set of differentially expressed proteins in molar tissues that could potentially be further examined as predictive biomarkers for the malignant transformation of CHMs. A molar proteome database was constructed and can be accessible online athttp://sysbio.chula.ac.th/Database/GTD_DB/Supplementary_Data.xlsx . Highlights: 2, 153 proteins were identified from all 28 specimens of hydatidiform mole. Compare between malignant and benign moles, 22 proteins were up-regulated. 10 proteins were significantly down-regulated. hCG, PSG3, GDF15, and ribosomal proteins are particularly promising. Expressed proteins in molar tissues may predict malignant transformation.